Efektivitas Metode Question Answer Relationships terhadap Kemampuan Membaca Pemahaman Peserta didik Kelas IV - Dyah Afifah Andari (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Abstrak: Kemampuan membaca pemahaman merupakan kemampuan menemukan arti kata, makna tersurat dan makna tersirat serta membuat kesimpulan. Kesulitan dalam mengidentifikasi gagasan pokok dalam bacaan terutama dalam membuat simpulan dialami oleh siswa kelas IV. Keefektifan metode Question Answer Relationships (QAR) terhadap kemampuan membaca pemahaman siswa kelas IV di MI 6 Tahun Tambakboyo Blitar menjadi fokus pada penelitian yang menggunakan pendekatan kuantitatif dengan jenis true experiement. Teknik pengumpulan data menggunakan instrumen tes. Hasil penelitian ini menunjukkan bahwa nilai thitung lebih besar dari ttabel pada signifikansi 0,05 (th = 3,824 >ttb = 1,171). Sehingga disimpulkan metode QAR efektif untuk meningkatkan kemampuan membaca pemahaman dibandingkan metode diskusi pada kelas kontrol.Abstract: Reading comprehension is the ability to capture the meaning of words, the ability to capture the explicit and implied meanings and the ability to draw conclusions. Fourth grade students have difficulty in identifying the main ideas in the reading, and they have not been able to draw conclusions. The purpose of this study is to determine the level of understanding before and after implementing Question-Answer-Relationship method and to measure its effectiveness in improving the reading comprehension of fourth grade students at MI (Islamic Primary School) 6 Tambakboyo Blitar. This study employed a quantitative approach, using a true experimental method. The data were collected using test instruments. The results of this study demonstrate that the value of t-observed is greater than t-table at a significance level of 0.05 (to = 3.824 > tt = 1.171). Hence, it can be concluded that the QAR method is effective for improving reading comprehension skills compared to the discussion method in the control class.